Morphology and stability of aggregates of an Oxisol according to tillage system and gypsum application - Fábio Régis de Souza (Revista Ceres, 2012)
Morphological characterization and aggregate stability is an important factor in evaluating management systems. The aim of this paper is to evaluate the stability and morphology of the aggregates of a dystrophic Oxisol managed with no-tillage and conventional tillage with and without the residual action of gypsum. The experimental design was randomized blocks arranged in split-split plot, where the treatments were two soil management systems (plots) with 0 and 2000 kg ha-1 of gypsum (subplots) and five depths (0-0.05, 0.05-0.10, 0.10-0.15, 0.15-0.20 and 0.20-0.30 m) as the subsubplots, with four replications. The aggregate morphology was determined through images and later evaluated by the Quantporo software. Stability was determined by the wet method. The results showed that the no-tillage system, with or without gypsum residual effect, provided the aggregates with the largest geometric diameters. The combination of no-tillage system and the gypsum residual effect provided rougher aggregates.